2016
DOI: 10.1021/jacs.6b06566
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding of 1,2-Azaborines in the Binding Cavity of T4 Lysozyme Mutants: Structures and Thermodynamics

Abstract: Protein crystallography and calorimetry were used to characterize the binding of 1,2-azaborines to model cavities in T4 lysozyme in direct comparison to their carbonaceous counterparts. In the apolar L99A cavity, affinity for Ab dropped only slightly versus benzene. In the cavity designed to accommodate a single hydrogen bond (L99A/M102Q), Gln102=O⋯H—N hydrogen bonding for Ab and BEtAb was observed in the crystallographic complexes. The strength of the hydrogen bonding was estimated as 0.94 and 0.64 kcal/mol f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 47 publications
(77 reference statements)
1
24
0
Order By: Relevance
“…In line with our work and Alkorta et al . study, Lee et al . have shown experimentally that 1,2‐azaborine may be inserted into the T4 Lysozyme mutant cavity through the O⋅⋅⋅H−N contact, what is of importance in classical aryl recognition pockets.…”
Section: Introductionsupporting
confidence: 92%
“…In line with our work and Alkorta et al . study, Lee et al . have shown experimentally that 1,2‐azaborine may be inserted into the T4 Lysozyme mutant cavity through the O⋅⋅⋅H−N contact, what is of importance in classical aryl recognition pockets.…”
Section: Introductionsupporting
confidence: 92%
“…BN/CC isosterism of arenes results in the so‐called azaborine heterocycles where specifically 1,2‐azaborines are designated as compounds with the boron and nitrogen atoms adjacent to each other (Figure ) . It has been demonstrated that 1,2‐azaborines can bind to aryl recognition pockets in biological targets and engage in hydrogen bonding inside those binding pockets . Furthermore, it has been shown that both the B ‐ and N ‐Et BN isosteres of ethylbenzene are inhibitors of ethylbenzene dehydrogenase (EbDH), in contrast to ethylbenzene itself, which is the naturally evolved substrate for the EbDH .…”
Section: Figurementioning
confidence: 99%
“…6 It has been demonstrated that 1,2-azaborines can bind to aryl recognition pockets 7 in biological targets and engage in hydrogen bonding inside those binding pockets. 8 Furthermore, it has been shown that both the B - and N -Et BN isosteres of ethylbenzene are inhibitors of ethylbenzene dehydrogenase (EbDH), in contrast to ethylbenzene itself, which is the naturally evolved substrate for the EbDH. 9 Despite the recent advances made in the area of azaborine chemistry, 10 the progress toward evaluating these heterocycles in the context of medicinal chemistry has remained underexplored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diatomic fragments BN and CC are isoelectronic and the chemical consequences of this simple relationship have been appreciated ever since the 1926 discovery of borazine which is isoelectronic to benzene and dubbed “inorganic benzene” (Figure ) . The substitution of a BN unit for a CC in an organic molecule has a transformative effect on the properties of the compound as illustrated by the three comparisons given in Figure from the fields of photochemistry, medicinal chemistry and hydrogen storage …”
Section: Figurementioning
confidence: 99%